STRATEGI PEMASARAN UMKM PANGAN LOKAL: STUDI PADA KERUPUK KULIT SAPI DI KECAMATAN CAKRANEGARA - Mariana, Mariana; Lale Ajeng Khalifatun Wardani (Yayasan Nusantara Hasana Berdikari, 2025)
The present study examines how product and promotion strategies influence consumer demand for beef crackers (kerupuk kulit sapi) in Cakranegara District, Mataram City. Employing a quantitative design with a survey method, data were gathered from 30 vendors chosen through purposive sampling. A Likert-scale questionnaire was used to collect responses, and multiple linear regression served as the analytical tool. The analysis reveals that product strategy exerts a significant impact on demand (p = 0.034 < 0.05), whereas promotion strategy shows no significant effect (p = 0.684 > 0.05). When considered together, however, both strategies significantly affect demand (p = 0.043 < 0.05). The determination coefficient (R² = 0.208) indicates that these two variables explain only 20.8% of demand variation, while the remaining 79.2% is attributed to other determinants beyond the scope of this study. The findings suggest that maintaining product quality and introducing innovations are crucial to sustaining consumer interest, while the adoption of digital promotion channels offers considerable opportunities to expand market reach and to align with the objectives of SDG 9 (Industry, Innovation, and Infrastructure).